2009
DOI: 10.1016/j.cpr.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder in African American children: What can be concluded from the past ten years?

Abstract: Samuel et al. [Samuel, V. J., Curtis, S., Thornell, A., George, P., Taylor, A., Brome, D. R., et al. (1997). The unexplored void of ADHD and African-American research: A review of the literature. Journal of Attention Disorders, 1(4), 197–207.] reviewed the literature on Attention Deficit Hyperactivity Disorder (ADHD) in African Americans, and found a paucity of research. The present review of 73 articles updates this assessment of available research and presents the current understanding of ADHD symptoms, asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
121
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 71 publications
(100 reference statements)
7
121
1
Order By: Relevance
“…9 However, whether and to what extent these disparities also occur among Hispanics and children of other races/ethnicities has not been systematically examined. 37,38 Our study extends previous work by establishing that children who are African-American, Hispanic, or of other races/ethnicities are less likely than whites to be diagnosed with ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 However, whether and to what extent these disparities also occur among Hispanics and children of other races/ethnicities has not been systematically examined. 37,38 Our study extends previous work by establishing that children who are African-American, Hispanic, or of other races/ethnicities are less likely than whites to be diagnosed with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Racial/ethnic minorities in particular have been reported to be diagnosed with ADHD at lower rates than white children, 7 and therefore may have unmet treatment needs. 8 Children who are African American are diagnosed with ADHD at only two-thirds the rate of white children despite displaying greater ADHD symptomatology, 9 and Hispanic children have also been reported to be underdiagnosed. 1 Less is known about diagnosis disparities for children of other races/ ethnicities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 The prevalence of ADHD between 1997 and 2006 was ϳ6.5%. 17 The CDC study 17 and other nationally representative studies 18,19 have revealed that ADHD prevalence is highest among poor children. Froehlich et al 18 reported an adjusted odds ratio of ADHD prevalence of 2.3 (95% confidence interval [CI]: 1.4 -3.9) for the poorest quintile compared with the wealthiest quintile.…”
Section: Adhdmentioning
confidence: 99%
“…Children in singlemother families are more likely to have ADHD compared to children in two-parent families (12% versus 8%) [2]. A review by Miller et al [3] found that African-American children have higher ADHD behavior ratings, while puzzlingly at the same time the reported incidence of ADHD is lower for African-American children, with African-American youth being diagnosed only about two-thirds as often as white children. Decreased access to and utilization of psychiatric services by the African-American community can potentially explain this pattern.…”
Section: Introductionmentioning
confidence: 99%